Structural Dynamic Analysis of the Chenderoh Dam Sector Gate Section - Ghazali M.H.M.; Zawawi M.H.; Hassan N.H.; Radzi M.R.M.; Mazlan A.Z.A.; Abas M.A.; Zainol M.R.R.M.A. (EDP Sciences, 2023)
Computer aided design; Dynamic analysis; Frequency response; Modal analysis; Natural frequencies; Sensitivity analysis; Structural dynamics; System theory; ANSYS software; CAD softwares; Dam structure; Dynamic characteristics; Frequency response functions; Maximum deflection; Mode shapes; Operational methods; Dams